Analisis Buku Ajar Bahasa Arab: Telaah Buku Arabiyyah Linnasyiin Dalam Perspektif Teori William Frances Mackey - Niswah MZ, Isniyatun (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
Interesting to study is the Arabic textbook Arabiyyah Linnasyiin This book will be further examined using William Francis Mackey's theory, which explains that a good textbook must fulfill three aspects: selection, gradation, presentation, and repetition. To achieve maximum research outcomes, this study employs a descriptive analysis method with a library research approach, where data sources are gathered from library materials such as books, journals, seminar proceedings, newspapers, and similar resources. The results of this study show that the Arabiyyah Linnasyiin textbook consists of four language skills: speaking (Muhadatsah), reading (maharah Qiroah), writing (maharah Kitabah), and grammatical analysis in the form of exercises (Ta'bir Syafahiyah). When viewed from the level of student learning, Arabiyyah li Nasyiin has six levels, consisting of Volume I, Volume II, Volume III, Volume IV, Volume V, and Volume VI. These levels are based on learning Arabic at the beginner, intermediate, and advanced levels. This book includes indicators and basic competency standards, though there is no set time limit. Secondly, in the Arabiyyah Linnasyiin textbooks, from the first to the sixth volume, the levels are categorized by themes, vocabulary, grammatical analysis, and the exercises provided. Thirdly, the Arabiyyah Linnasyiin textbook is comprehensive in terms of covering the four aspects of Arabic language skills, with content that includes maharah kalam, maharah qiroah, maharah kitabah, and grammatical analysis in the form of exercises. In terms of procedure, the Arabiyyah Linnasyiin textbook uses a pictorial procedure, a teaching method that employs images. Fourth, regarding speaking, from Volume I to Volume VI, the speaking-related material is extensive and complete, corresponding to the levels and themes provided. For reading, the reading themes maharah qiroah in Volumes I to VI are dense and thorough, appropriate to the students' level of proficiency. In terms of writing, the writing-related material in Arabiyyah Linnasyiin is only provided in Volume I, and this is tailored to the students' proficiency level in learning Arabic.